Medios de comunicación privados y oposición política. - Lizarzaburo Palomino, Renata Gabriela (2016)
In Ecuador the private media have historically been linked to major economic groups. This connection allowed them to establish business with the State to live in harmony with it and also enjoy a kind of legal immunity. When Rafael Correa was elected as president in 2007 this situation changed for the private media, as his government plan featured a media property regularization, and the development of a communication law aimed to regulate the practice of journalism. These transformations generated resistance among the media, which insisted to defend its status quo launching a frontal attack against the president. The media had stopped doing journalism to get involved in politics and they forgot their duty to inform, entertain and educate. Now they openly defend the social sectors they represent. The analysis of several documents about the private media in the country allowed to determine that the media has assumed a role that is not theirs. They are not legitimate representatives of society. It is true that policies and laws made by Correa are a historic step forward in the democratization of communication, but there is still much to do, to build media at the service of society.